Windows Shopping Learning Strategy Assisted by Mind Mapping for Learning Activeness - Widyasanti, Ni Putu; Windayani, Ni Luh Ika (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Low learning engagement occurs in every level of education; this is a concern in improving the quality of education, especially at the tertiary level in the cognitive development method course for Early Childhood Education (AUD). This study aims to examine the effectiveness of the Windows Shopping learning strategy combined with the Mind Mapping technique in improving student learning engagement. This study uses a quantitative approach with a quasi-experimental method with a pretest-posttest control group design. The subjects of the study were 50 students taking the cognitive development method course for Early Childhood Education (AUD). The sample was divided into experimental and control groups. The experimental group received learning using Windows Shopping assisted by Mind Mapping, and the control group was taught using conventional learning methods. The instrument used was a validated observation sheet. Data analysis was carried out using Analysis of Covariance (ANCOVA). The results of the analysis showed that there was an effect of using the Windows Shopping strategy assisted by Mind Mapping, significantly increasing learning engagement compared to conventional learning methods. The implications of these results indicate the importance of implementing the Windows Shopping learning strategy assisted by visual Mind Mapping to increase student engagement in the learning process.